OPTIMIZATION POSSIBILITIES IN FINAL PRODUCTS INVENTORY SERVICES - Juhász, János (Advanced Logistic Systems - Theory and Practice, 2021)
My study is focusing on the internal companies’ logistics services to increase the efficiencies of final products inventory. Competitiveness and effectiveness are important factors in the manufacturing and services processes, where are needed to serve out the whole logistics networks for different sectors. My article provides an integrated overview of the fictitious company' final products inventory activities and its intensification. There are three related area of the inventory activities: packaging, forms of final products load and the related vehicle unit services. This paper shows alternative solutions to improve the sensitivity of the final products processes. The methodology enables to find the right resource allocations for the efficient operation in the service of inventory operation.